Construction solid waste management practice - Husin, Nur Illiana; Che Ahmad, Asmalia; Abdul Tharim, Asniza Hamimi (2013)
Generally, construction solid waste is produced from new construction, demolition or renovation work. The common type of the construction solid waste produced are wood, concrete, paint, brick, roofing tiles, tiles, plastic and many more.Proper management and better planning are needed to control, reduce or minimize the quantity of construction solid waste during construction. This research is conducted to investigate the status of construction solid waste management at construction sites. In order to achieve this aim, several objectives have been determined for this research. The first objective is to identify types of the construction solid waste produce at construction sites. The second objective is to investigate the management practices of the construction solid waste at construction site.The final objective is to determine the amount of construction solid waste produced in the different types of construction sites.However, this paper presents an overview of the construction solid waste management practice at construction sites as this research is in the preliminary phase.The methodology that will be used for this research is mixed methods.This method is combination of quantitative and qualitative data collections.For the quantitative method, questionnaire will be distributed to contractors in order to achieve the first and second objectives. For qualitative methods, observations at site will be conducted at commercial, residential, infrastructure and mixed development construction sites to attain the third objective.This research will be conducted at the central region of peninsular Malaysia such as Selangor, Kuala Lumpur and Putrajaya.These locations are chosen due to its immense construction and development areas.This research hopes to contribute knowledge on construction waste management practices in our country.